2016
DOI: 10.1103/physrevd.93.023513
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological hints of modified gravity?

Abstract: The recent measurements of Cosmic Microwave Background temperature and polarization anisotropies made by the Planck satellite have provided impressive confirmation of the ΛCDM cosmological model. However interesting hints of slight deviations from ΛCDM have been found, including a 95% c.l. preference for a "modified gravity" structure formation scenario. In this paper we confirm the preference for a modified gravity scenario from Planck 2015 data, find that modified gravity solves the so-called A lens anomaly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 91 publications
(123 reference statements)
4
86
0
Order By: Relevance
“…4 Given the Planck T T , T E, EE + lowP dataset, this is the significance with which the ΛCDM + α s + β s model is preferred over the ΛCDM one. Going back to Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Given the Planck T T , T E, EE + lowP dataset, this is the significance with which the ΛCDM + α s + β s model is preferred over the ΛCDM one. Going back to Tab.…”
Section: Resultsmentioning
confidence: 99%
“…A value of A L larger than one is difficult to accommodate in ΛCDM, and several solutions have been proposed as modified gravity [4,5], neutrino anisotropies [6], and compensated isocurvature perturbations [7]. Combining Planck with data from the Atacama Cosmology Telescope (ACT) and the South Pole Telescope (SPT) to better constrain the foregrounds, Couchot et al [8], found a consistency with A L = 1.…”
Section: Introductionmentioning
confidence: 99%
“…Daniel et al 2010;Johnson et al 2016;Ade et al 2016b;Di Valentino, Melchiorri & Silk 2016a). To this end, we use ISITGR (Dossett, Ishak & Moldenhauer 2011;Dossett & Ishak 2012), which is an integrated set of modified modules in COSMOMC designed to test gravity on cosmic scales.…”
Section: Modified Gravitymentioning
confidence: 99%
“…This CFHTLenS-Planck discordance has been explored in the context of extensions to the standard ΛCDM model and systematic uncertainties in the lensing measurements (e.g. MacCrann et al 2015;Köhlinger et al 2015;Kunz, Nesseris & Sawicki 2015;Leistedt, Peiris & Verde 2014;Battye, Charnock & Moss 2015;Enqvist et al 2015;Di Valentino, Melchiorri & Silk 2016a;Dossett et al 2015;Joudaki et al 2017;Liu, Ortiz-Vazquez & Hill 2016;Alsing, Heavens & Jaffe 2016). Meanwhile, lensing observations by the Deep Lens Survey (DLS, Jee et al 2016) exhibit a mild discrepancy with KiDS (at ∼ 1.5σ in S8), and observations by the Dark Energy Survey (DES, Abbott et al 2016) have sufficiently large uncertainties that they agree both with CFHTLenS/KiDS and Planck.…”
Section: Introductionmentioning
confidence: 99%
“…The only solution for the model is to modify the computation of the geodesic deflection, i.e. to modify standard GR (Hu & Raveri 2015;Di Valentino et al 2016). For the data, since Planck maps undergo a complicated treatment (for an overview see Planck Collaboration I 2016), one cannot exclude small residual systematic effects that could impact the details of the likelihood function in a different way from one implementation to the other.…”
Section: Introductionmentioning
confidence: 99%